Pentingnya Penerapan Strategik Manajemen Di Rumah Sakit: Kajian Teoritis - Made Santika; Vip Paramarta; Ittang Somba (Pusat Riset dan Inovasi Nasional, 2023)
Hospital service institutions should understand how appropriate strategic management is to make their business stronger. This is important so that the process of making every decision is in accordance with the hospital's vision and mission. Strategic management provides overall direction for a company and is closely related to the field of organizational behavior. Current strategic management must provide a basic foundation or guideline for decision making within an agency. The aim of this theoretical study is to find out how important strategic management is in hospitals. The research method used is descriptive theoretical study, namely a method that discusses several possibilities for solving actual problems by collecting data, compiling or classifying it, analyzing and interpreting it with existing theories and comparing it from literature sources. The results of the study show that the importance of strategic management in hospitals is to design basic finances, plan forecasts, plan external strategies, and strategic management in hospital marketing. It can be concluded that strategic management requires leadership skills that are able to make major decisions, overcome existing obstacles or problems, and take full advantage of opportunities. In Hospital Agencies, strategic management is carried out continuously, meaning it is sustainable by evaluating and also controlling internal business, conducting competitor analysis, and establishing strategies to be able to compete with other hospitals and have excellent programs that can improve service quality and patient satisfaction. For hospital agencies, it should be able to be applied by all management and service parties so that they can face competition and show the excellence of the hospital and improve service quality.